1997
DOI: 10.1111/j.2042-7174.1997.tb00877.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the appropriateness of prescribing in nursing homes

Abstract: A study carried out in five nursing homes and 13 general practitioner practices in the North West National Health Service region investigated medicine use in the homes and assessed the extent of inappropriate prescribing using consensus derived criteria. A review of the medical and nursing records of 101 residents showed that they were using a total of 714 items (mean 7.1; range 0 to 15), of which 659 were medicines, including 51 dressings, and 55 were other items such as stoma products. When criteria for inap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…These values are lower than that for residents in the USA, where the mean is six to seven drugs per patient (Beers et al, 1992). The USA ®gure is similar to the UK, where residents in Northamptonshire nursing homes took a mean of 6.6 drugs (range 1±19) (Corbett, 1997) and residents in the North West region took 6.5 drugs (range 0±14) (Lunn et al, 1997). Nolan and O'Malley (1989) quote diuretics, analgesics, potassium salts, cardiac glycosides and laxatives as the most commonly prescribed nonpsychotropic drugs and this is similar to the most common non-psychotropic drugs prescribed in North and West Belfast (Passmore et al, 1995).…”
Section: Non-psychotropic Medicationmentioning
confidence: 84%
See 1 more Smart Citation
“…These values are lower than that for residents in the USA, where the mean is six to seven drugs per patient (Beers et al, 1992). The USA ®gure is similar to the UK, where residents in Northamptonshire nursing homes took a mean of 6.6 drugs (range 1±19) (Corbett, 1997) and residents in the North West region took 6.5 drugs (range 0±14) (Lunn et al, 1997). Nolan and O'Malley (1989) quote diuretics, analgesics, potassium salts, cardiac glycosides and laxatives as the most commonly prescribed nonpsychotropic drugs and this is similar to the most common non-psychotropic drugs prescribed in North and West Belfast (Passmore et al, 1995).…”
Section: Non-psychotropic Medicationmentioning
confidence: 84%
“…In the UK there are relatively few data on use of psychotropic drugs in nursing homes. Lunn et al (1997) describe 26% of their population as using`central nervous system' drugs as de®ned in the British National Formulary, although this grouping includes antiepileptics and analgesics. Snowdon et al (1995) showed psychotropic drug use to be 59% in central Sydney nursing homes.…”
Section: Psychotropic Drug Usementioning
confidence: 99%
“…In 1997, Lunn et al 7 developed a set of 18 explicit criteria, based on expert opinion, to identify inappropriate prescribing in 101 nursing home residents in the UK. For 7 of the 18 criteria, information on clinical status or diagnoses of the residents was necessary, again making them unsuitable for use with pharmacy prescription data only, although some of them could be incorporated.…”
Section: Wwwtheannalscommentioning
confidence: 99%
“…In England, Lunn et al (1997) describe 26% of their population to be using 'central nervous system' drugs as defined by the British National Formulary (BNF; British Medical Association & Royal Pharmaceutical Society of Great Britain, 2002), but this definition includes anti-epileptics and analgesics. In 1995, Snowdon et al reported that psychotropic drug use in Australian nursing homes was 59%, although this figure has fallen in recent years (Snowdon, 1999).…”
Section: Psychotropic Medicationmentioning
confidence: 99%
“…In a study carried out in England, a physician (in elderly care), a general practitioner (GP), a pharmacist and a clinical pharmacologist developed criteria for inappropriate prescribing and these were then applied to the medication regimes of 101 residents (Beers et al, 1992). It was found that 53% of residents had at least one inappropriate prescription, with cardiovascular and central nervous system drugs being implicated most often (Lunn et al, 1997).…”
Section: Non-psychotropic Medicationmentioning
confidence: 99%